1987
DOI: 10.1159/000284473
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa in Italy: Clinical Features and Outcome in a Long-Term Follow-Up Study

Abstract: Fifty-five patients with a diagnosis of anorexia nervosa hospitalized between 1970 and 1975 in the Departments of Psychiatry and Internal Medicine of the University of Padua were recalled between 1981 and 1983. Forty patients (73%) participated in this follow-up study. At follow-up, using the criteria of Garfinkel et al., 15 patients (37.5%) had an ‘excellent’ outcome, 10 (25 %) were ‘much improved’, 7(17.5%) were ‘symptomatic’, 6(15 %) had a ‘poor’ outcome and 2 (5%) were deceased. There was, generally, a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
2
6
0
1
Order By: Relevance
“…From Table 6 the results of the present study were similar to those of Santonastaso et al (1987) and Toner et al (1986), who had similar lengthy follow-up periods. The other two studies had shorter duration of follow-up and fewer subjects showed excellent status.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…From Table 6 the results of the present study were similar to those of Santonastaso et al (1987) and Toner et al (1986), who had similar lengthy follow-up periods. The other two studies had shorter duration of follow-up and fewer subjects showed excellent status.…”
Section: Discussionsupporting
confidence: 84%
“…A more precise comparison is possible with those studies that have utilised the Global Clinical Score as a summary measure of global outcome. Five studies (including the present study) have reported results for similar subject samples of young females, receiving a multicomponent style of treatment (Garfinkel et al, 1977;Nussbaum, Shenker, Baird, & Saravay, 1985;Santonastaso, Favaretto, & Canton, 1987;Toner, Garfinkel, & Garner, 1986). The percentage of subjects falling into the different outcome groups is displayed in Table 6.…”
Section: Discussionmentioning
confidence: 71%
“…Hsu et al (1979) described the sexual function of 17% of women in a 4‐ to 8‐year follow‐up as “clearly abnormal,” with a positive correlation between “good” ED recovery and better sexual adjustment. In a 6‐year follow‐up study, Santonastaso et al (1987) found that almost all women with AN in the “symptomatic” or “poor” long‐term outcome category reported “unsatisfactory” or “absent” sexual relations, whereas only a few individuals reported the same sexual complaints in the “excellent” or “much improved” ED outcome categories. Morgan et al (1995) found “sexual discord” in the current relationship of 40% of women with EDs included in a 2‐year follow‐up study, whereas Castellini and colleagues found the sexual function of women with EDs to improve significantly overtime.…”
Section: Resultsmentioning
confidence: 99%
“…This fundamentally restricts the generalizability of the findings summarized in this review, limiting our ability to comment on the sexual function and dysfunction experiences of more diverse samples of individuals with AN. Only two of the included studies reported information pertaining to the social class of the included sample (Hsu et al, 1979; Santonastaso et al, 1987), and associations between class, EDs, and sexual outcomes were poorly elaborated upon. Future research should aim to develop our understanding of EDs and associated sequelae across a more diverse range of individuals.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Our case, encountered during a follow-up study on AN (Santonastaso, Favaretto, & Canton, 1987), concerns a patient who presented dysmorphophobia 9 years after the onset of AN.…”
mentioning
confidence: 99%